The Level of Critical Thinking Skills of High School Students in Physics Learning Based on Local Wisdom - Mahir Mahir; M. A. Martawijaya (Jurnal Edukasi Terkini, 2025)
Purpose-This study aims to investigate the level of high school students' critical thinking skills in physics learning by incorporating local wisdom. It highlights the significance of integrating cultural context into science education to enhance students' cognitive engagement and deepen their conceptual understanding. Research Methodology/Design/Approach-A quantitative descriptive survey was conducted involving high school students enrolled in a physics class that applied local wisdom as a contextual learning approach. Data were collected using a critical thinking skills test developed based on Ennis’ five indicators of critical thinking. The collected data were then analyzed descriptively to evaluate students’ performance across each critical thinking indicator. Findings- The results revealed that students’ overall critical thinking skills were at a moderate level, with an average score of 62.36%. Among the five indicators, the highest performance was observed in "giving simple explanations" (68.2%), while the lowest was in "making further explanations" (57.3%). These findings suggest that although students are able to connect physics concepts to local phenomena, their ability to engage in deeper reasoning and advanced critical thinking still requires further pedagogical reinforcement. Originality / Value- This study contributes to the growing body of literature on contextual science education by emphasizing the role of local wisdom in fostering critical thinking skills. Unlike prior studies that focused on general instructional models, this research provides empirical evidence supporting the potential value of culturally integrated learning in the physics classroom, particularly in developing students’ higher-order thinking skills.